Checklist for the insect fauna of two East Sea Islands (Ulleungdo Is. and Dokdo Is.) in the Republic of Korea - Lee, Dong-Yeol; Jeong, Ilyeong; Kim, Seonmin; Choi, Jae Won; Won, Min Hyeok; Kim, Donguk; Kim, Dongmin; Kim, Young-Kun; Jeon, Jiseung; Ryu, Jihun; Bang, WooJun; Chang, Jun Hyuk; et al. (Biodiversity data journal, 2024)
Ulleungdo and Dokdo, located in the East Sea, are volcanic islands with high ecological value due to their unique biodiversity. Although research on the insect fauna on these two Islands has been conducted from the early 19 th century to recent times, limitations exist due to several issues, including misidentifications and historical errors. This study addresses these issues by conducting a comprehensive insect survey from 2020 to 2023, re-identifying misidentified specimens and compiling references to create an updated and accurate checklist of insect species for Ulleungdo and Dokdo. The checklists include 20 orders, 227 families and 1694 species, including 28 previously unrecorded species for Ulleungdo Island: Neoitamus cothurnatus univittatus (Loew, 1871), Elachiptera insignis (Thomson, 1869), Elachiptera sibirica (Loew, 1858), Muscina levida (Harris, 1780), Orchisia costata (Meigen, 1826), Ensina sonchi (Linnaeus, 1767), Armigeres subalbatus (Coquillett, 1898), Aedes koreicus (Edwards, 1917), Aedes galloisi Yamada, 1921, Aedes albopictus (Skuse, 1894), Aedes togoi (Theobald, 1907), Stenolophus difficilis (Hope, 1845), Dasytes vulgaris Nakane, 1963, Attalus elongatulus Lewis, 1895, Elacatis kraatzi Reitter, 1879, Polygraphus jezoensis Niisima, 1909, Scolytoplatypus tycon Blandford, 1893, Ambrosiophilus atratus (Eichhoff, 1876), Psilarthroides czerskyi (Zaslavskij, 1956), Tomoxia nipponica Kôno, 1928, Adelphocoris demissus Horvath, 1905, Corythucha marmorata (Uhler, 1878), Spilarctia seriatopunctata suzukii Inoue & Maenami, 1963, Hypopyra vespertilio (Fabricius, 1787), Simplicia rectalis (Eversmann, 1842), Acronicta hercules (Felder & Rogenhofer, 1874), Analetia postica (Hampson, 1905) and Eudemis brevisetosa Oku, 2005; 10 orders, 80 families and 201 species, including three unrecorded species for Dokdo Island: Arhopaloscelis bifasciata (Kraatz, 1879), Nabis stenoferus Hsiao, 1964 and Haplogonatopus oratorius (Westwood, 1833).